ANALYSIS OF COLLEGE STUDENTS’ SPEAKING SKILL IN VIDEO PROJECT PUBLISHED ON YOUTUBE - Zega, Riswan; Halawa, Mercy Dwiyul; Hulu, Nesti Arni; Gulo, Benedikta; Telaumbanua, Enjel Tris Jelita; Ndruru, Ednis Sartika; Zai, Novita Purnawirati (STKIP Siliwangi, 2024)
This study aimed to analyze the impact of video projects on YouTube to improve students' speaking skills. This study used descriptive quantitative research. The population of this study was 42 second semester students of English Education Study Program at University of Nias. To determine the sample researchers used simple random sampling then the sample of this study was 20 people. The data were collected by using documentation and observation techniques. The data was in the form of videos made and uploaded by the students with three different topics. Students’ videos have three different topics namely registration, giving opinions and arriving late. The videos were observed and scored based on the speaking assessment rubric by Helmanda & Nisa (2018). After that, the scores obtained by students from each video were categorized. The researchers examined the video projects uploaded by second-semester students to analyze the impact of video uploading on improving students’ speaking skills. The result showed that students’ video project can improve students’ speaking skill. Thus, it is suggested for future researchers to conduct a longitudinal study to examine the long-term impact of using YouTube video projects in improving students' speaking skills.